Brain temperature in healthy and diseased conditions: A review on the special implications of MRS for monitoring brain temperature - Yulug, Burak; Velioğlu, Halil Aziz; Sayman, Dila; Çankaya, Şeyda; Hanoğlu, Lütfü (Elsevier Masson s.r.l., 2023)
Brain temperature determines not only an individual's cognitive functionality but also the prognosis and mortality rates of many brain diseases. More specifically, brain temperature not only changes in response to different physiological events like yawning and stretching, but also plays a significant pathophysiological role in a number of neurological and neuropsychiatric illnesses. Here, we have outlined the function of brain hyperthermia in both diseased and healthy states, focusing particularly on the amyloid beta aggregation in Alzheimer's disease.
Keywords: Brain Temperature; Entropy; Temperature Monitoring